Kapriciozne plati Haydnovega kvarteta - Hansell, Sven H. (Muzikološki zbornik, 2007)
Haydn's Quartet op. 9, no. 6, illustrates the application of poetic conventionsto music. Viewed as a Capriccio, movement 1 discloses a labyrinthine rhythmic structure both didactic and amusing. A table of musical rhythms and inventory of musical phrase types supplement analyses.
Keywords: capriccio; fraza; glasba; glasbeno-poetske strukture; godalni kvartet; Haydn, Joseph, 1732-1809; music; ritmika